In the Footsteps Left by The Normativity of Letters in Children (2022)
The study shows how the norms of the Ministry of National Education in the process of teachingand learning to read and write are evident in the conceptions and practices of the transitionteachers in the educational institution Sagrado Corazón de Jesús, in the Municipality ofFilandia Quindío. The ethnographic design considered the perspectives of teachers, studentsand parents in a holistic way. It was concluded that the teachers develop the playfulness andpedagogical projects from the normative, and integrate traditional activities of preparation,juxtaposed with others of constructivist intention, as well as the importance of characterizingthe parents in the process.